Autonomy and Turnover in Distributed Software Development Projects: a Systematic Literature Review - Chaves, Amanda; Amorim, Luís; Marinho, Marcelo; Farias Júnior, Ivaldir de; Moura, Hermano (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2022.20966, 2022)
Distributed teams have become a tendency among software companies. However, companies that apply Distributed Software Development (DSD) suffer from high developer turnover. Research shows that autonomy factors can mitigate or prevent team turnover. In this research, we investigate the role of autonomy on turnover in distributed teams through a Systematic Literature Review (SLR). Our findings revealed a set of autonomy dimensions that influence turnover in DSD projects. Besides, we identified the main factors related to autonomy linked to turnover in DSD projects. These findings provide software companies and organizations with a better understanding of the importance of autonomy factors to battle the DSD projects turnover problem.